2022
DOI: 10.3390/w14030306
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Pressures and Risk of Cavitation in Steeply Sloping Stepped Spillways of Large Dams

Abstract: Stepped spillways have been increasingly used to handle flood releases from large dams associated with hydropower plants, and it is important to evaluate the fluctuating pressure field on the steps. Hydraulic model investigations were conducted on three 53° (1V:0.75H) sloping and relatively large-stepped chutes to characterize the mean, fluctuating, and extreme pressures acting on the most critical regions of the step faces, near their outer edges. The pressure development along the chutes is presented, genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
(119 reference statements)
0
9
0
Order By: Relevance
“…Besides the estimate performed using SpillwayPro for the cavitation indices based on Equation 3, it was decided, for comparative purposes, to determine the index σc by utilizing the friction factor " f " as described in Equations 4 and 5 (Arndt & Ippen, 1968;Falvey, 1990;Frizell et al, 2013;Kermani et al, 2013;Matos et al, 2022). (5)…”
Section: /11mentioning
confidence: 99%
See 3 more Smart Citations
“…Besides the estimate performed using SpillwayPro for the cavitation indices based on Equation 3, it was decided, for comparative purposes, to determine the index σc by utilizing the friction factor " f " as described in Equations 4 and 5 (Arndt & Ippen, 1968;Falvey, 1990;Frizell et al, 2013;Kermani et al, 2013;Matos et al, 2022). (5)…”
Section: /11mentioning
confidence: 99%
“…It is known that index c, estimated from the friction factor proposed for roughnesses uniformly distributed in turbulent boundary layers was widely used in the studies of Arndt (1981), Falvey (1990), Frizell et al (2013) and Matos et al (2022). Frizell et al (2013) and Matos et al (2022) used Equation 4to estimate the occurrence and location of greatest activity of the cavitation phenomenon in spillways with steep slope steps (1V:0.75H).…”
Section: /11mentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of the water flow pattern, Chanson [2] and Ohtsu et al [3] proposed the boundary equations of the step nappe flow and skimming flow regime. In terms of step pressure characteristics, Mator et al [4], Sanchez-Juny et al [5], and Amador et al [6] analyzed the pressure variation law on the horizontal and vertical surfaces of the steps, and found that negative pressure is generated on the vertical surface of the step near the convex corner position, and this area of negative pressure is prone to producing cavitation hazards, which was verified in the experiments of Frizell et al [7]. In actual projects, cavitation has also occurred to varying degrees in step spillways, such as the New Croton Dam in the United States, the Dona Francisca Dam in Brazil [8], the Danjiangkou Hydropower Station [9], and the step spillway in the Suofengying Hydropower Station [10] in China.…”
Section: Introductionmentioning
confidence: 99%